Rancang Bangun Aplikasi Web Profil Dan Kotak Saran Siswa/I Sma Negeri 1 Kurun Berbasis Website - Widiatry, Widiatry; Yosepha, Elsa (Journal of Information Technology and Computer Science, 2022)
SMA Negeri 1 Kurun is one of the largest high schools in Kuala Kurun, Gunung Mas Regency. Public SMA is run by the government. Since the implementation of regional autonomy in 2001, the management of public high schools in Indonesia, which was previously under the Ministry of National Education, is now the responsibility of the provincial government. Based on this, a website-based Web Application Design for Profile and Suggestion Box for SMA Negeri 1 Kurun is made, which aims to provide information to the general public about SMA Negeri 1 Kurun and as a means of conveying criticism of suggestions from students. The methodology used in making this website is a waterfall, with stages, namely the Requirements Definition stage described using a flowchart, Requirements Analysis and Definition described through DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and database. Implementation and Unit Testing with the programming languages used, namely HTML, PHP, CSS, Bootstrap, Javascript, and MySQL, Integration and System Testing using the Blackbox Method. On this website there are several features, namely homepage, school profile, extracurricular, SIAP data, Lists for Students, Announcements, Albums and for Students. As well as for students it has additional features, such as criticism of suggestions for students. With the aim that the public can get information about SMA Negeri 1 Kurun quickly and students have a forum for delivering constructive criticism for SMA Negeri 1 Kurun.